Dectin-1 Is Required for Resistance to Coccidioidomycosis in Mice - Suganya Viriyakosol (American Society for Microbiology, 2013)
ABSTRACT We assessed the role of Dectin-1 in the immune response to the pathogenic fungus Coccidioides, both in vitro and in vivo, using mice with a targeted mutation in Clec7a. Elicited peritoneal macrophages responded to formalin-killed spherules (FKS) and alkali-treated FKS by secreting proinflammatory cytokines in a Dectin-1- and β-glucan-dependent manner. The responses of bone marrow-derived dendritic cells (BMDC) to the same stimulants were more complex; interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-α) secretion was independent of Dectin-1, while IL-6, IL-10, and granulocyte-macrophage colony-stimulating factor (GM-CSF) were largely but not entirely dependent on Dectin-1. After intranasal infection, Dectin-1−/− mice had lower concentrations of IL-12p70, gamma interferon (IFN-γ), IL-1β, and the Th17 cytokines IL-22, IL-23, and 17A in the lung lavage fluid, which may explain why they were significantly more susceptible to pulmonary coccidioidomycosis two weeks after infection. The Dectin-1 mutation was even more deleterious in (B6 × DBA/2)F2 mice, which are more resistant to coccidioidomycosis than B6 mice by virtue of protective genes from DBA/2, a genetically resistant strain. We also found that two susceptible strains of mice (B6 and BALB/c) expressed much less Dectin-1 in their lungs than did resistant DBA/2 mice. We conclude that Dectin-1 is necessary for resistance to Coccidioides immitis, that Dectin-1 promotes both Th1 and Th17 protective immune responses to this infection, and that there is a correlation between expression of Dectin-1 by the inflammatory infiltrate and resistance to coccidioidomycosis. IMPORTANCE Coccidioidomycosis is a fungal infection endemic in the southwestern United States and neighboring Mexico, causing ~150,000 lung infections in people and resulting in ~17,000 hospitalizations annually in California alone. Very little is known about innate immunity to this fungus. This paper shows that Dectin-1, the primary β-glucan receptor on myeloid cells, is required for resistance to this pathogen. Dectin-1 is part of the innate immune system, and it is needed to direct the acquired immune response toward into a pathway that will lead to macrophage activation. Lungs from infected mice lacking Dectin-1 had lower concentrations of Th1 and Th17 cytokines, two cytokine pathways that are very important for acquired T cell immunity to Coccidioides spp. This is the first demonstration that Dectin-1 is required for host resistance to a dimorphic, primary pathogenic fungus.